Performance of Broiler Chicken as Affected by Replacement of Maize with Pearl Millet and Broken Rice Mixture in the Diet - Bala, Suman; Sharma, R. K.; Khan, Nazam; Rastogi, Ankur; Haq, Zulfqarul (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted on three hundred and twenty, one day old commercial broiler chicks (Cobb strain) to study the effect of replacement of maize by graded levels of pearl millet and broken rice mixture (PBM) on their performance. The birds were randomly divided into four groups (80 birds/group). The experimental diets were: 0% maize replacement (T1), 25% maize replacement with PBM (T2), 50% maize replacement with PBM (T3), 75% maize replacement with PBM mixture (T4). The diets formulated were isocaloric and isonitrogenous as per ICAR (2013). Experiment was conducted for 42 days. The body weight gain (g) was significantly (P